Feasibility of liver stiffness measurement in morbidly obese patients undergoing bariatric surgery using XL probe. (2nd October 2016) - Weiss, Johannes; Rau, Monika; Meertens, Jan; Hering, Ilona; Reichert, Lisa; Kudlich, Theodor; Koschker, Ann-Kathrin; Jurowich, Christian; Geier, Andreas
Abstract: Objective: Prevalence of non-alcoholic fatty liver disease is rising in the Western world and reaches up to 90% in patients undergoing bariatric surgery. Fibroscan ® as a non-invasive tool for liver stiffness measurement (LSM) has several limitations in morbidly obese patients. Only few data exist about the technical feasibility and accuracy of LSM in these patients. We aimed to analyse the feasibility of LSM by Fibroscan ® in bariatric patients. Materials and methods: In morbidly obese patients, LSM was performed using XL probe. Measurements were termed reliable if 10 successful measurements with a success rate ≥60% and an interquartile range/median (IQR/M) <0.3 were obtained, unreliable if 10 successful measurements were obtained but the IQR/M was >0.3, and they were termed failed if they were neither reliable nor unreliable. Results: A total of 149 patients were included (87 with liver biopsies); mean BMI was 51.6 ± 8.5 kg/m 2 . In 41% LSM using XL-probe was reliable, in 22% unreliable and in 37% failed. Failed LSM was significantly more frequent in patients with higher BMI compared to reliable and unreliable measurements ( p  < 0.05). In patients with failed measurement, sonographic paramedian and intercostal distances were significantly higher compared to reliable measurements. All three patients with F4 fibrosis could successfully be differentiated by LSM from patients without fibrosis. Conclusions: LSM with XL probe is feasible in almost two-thirds of morbidly obese patients with a BMI ≥50 kg/m 2 . Reliable prediction of advanced fibrosis appears to be possible even if formal criteria of successful measurements are not met.